G-106 Mucosal vaccination with a replication-competent VSV-HIV chimera delivering Env trimers protects rhesus macaques from rectal SHIV infection. (March 2017) - Parks, Christopher
Abstract : Multiple licensed vaccines are based on live attenuated enveloped viruses. Because these vaccines cause a mild infection, they effectively direct immune responses against authentic viral targets, including multimeric transmembrane glycoproteins arrayed on the surface of infected cells and virus progeny. To develop a vaccine that would mimic transmembrane Env presentation that occurs during an HIV infection, we used vesicular stomatitis virus (VSV) to generate a replication-competent VSV-HIV chimera (VSV[INCREMENT]G-EnvG) in which the native VSV glycoprotein (G) was replaced with subtype A HIV Env from strain BG505. Ten Indian rhesus macaques were vaccinated with VSV[INCREMENT]G-EnvG by applying live vaccine to intranasal and intraoral surfaces after which all animals developed Env antibodies. Seven of 10 vaccinated macaques were protected from 10 sequential intrarectal challenges with heterologous subtype B SHIV SF162p3 while 9 of 10 unvaccinated controls became infected resulting in 67% efficacy (P = 0.014). Although significant HIV pseudovirus neutralization activity was not detectable in serum from vaccinated macaques, protection was associated with Env-specific binding antibodies. Importantly, contrasting results were produced in a third study group vaccinated with a different VSV vector (VSV-G6-EnvG), which expressed the same Env immunogen as well as G. VSV-G6-EnvG also elicited Env antibodies but failed to induce protective immunity. Neither VSV-based vaccine evoked a strong anti-Env cellular immune response detectable in peripheral blood. These results indicated that protection from SHIV infection induced by VSV[INCREMENT]G-EnvG was associated with Env-specific binding antibodies but not T cells. Furthermore, the differing efficacy of the 2 types of VSV-based vaccines indicated that vector design significantly modulated the qualities of the polyclonal antibody response.